Prevalence of IgM and IgG antibodies to SARS-CoV-2 in health care workers at a tertiary care New York hospital during the Spring COVID-19 surge - Talbot, Lillian R. (Perioper Med (Lond), 2021)
BACKGROUND: Health care workers (HCW) such as anesthesiologists, surgeons, and intensivists face high rates of exposure to SARS-CoV-2 through direct contact with COVID-19 patients. While there are initial reports of the prevalence of COVID-19 antibodies among the general population, there are few reports comparing the seroprevalence of IgM/IgG COVID-19 antibodies in HCW of different exposure levels as well as different HCW professions. METHODS: A convenience sample of health care workers provided blood for COVID-19 antibody testing and a review of medical history and work exposure for correlative analyses. RESULTS: Overall, 474 HCW were enrolled in April 2020 including 102 front-line physicians (e.g., anesthesiologists, surgeons, intensivists, emergency medicine), 91 other physicians, 135 nurses, 134 other clinical staff, and 12 non-clinical HCW. The prevalence of IgM or IgG antibodies to SARS-CoV-2 was 16.9% (95% CI 13.6–20.6) (80/474). The proportion of positive antibodies in the PCR + group was significantly higher than health care workers without symptoms (84.6% [95% CI 54.6–98.1] vs. 12.3% [95% CI 8.5–17.2], p < 0.001). No significant differences in proportions of COVID-19 antibodies were observed among the different exposure groups (e.g., high vs minimal/no exposure) and among the different HCW professionals. CONCLUSIONS: Despite exposure to COVID-19 patients, the prevalence of antibodies in our HCW was similar to what has been reported for the general population of New York State (14%) and for another New York HCW cohort (13.7%). Health care workers with higher exposure rates were not more likely to have been infected with COVID-19. Therefore, these data suggest that infection of HCW may result from exposure in the community rather than at work. TRIAL REGISTRATION: This investigator-initiated study was observational; therefore, no registration was required. Not applicable. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13741-021-00177-5.